Keterlibatan Orangtua dalam Pendidikan dan Komitmen Siswa terhadap Sekolah: Studi Meta-analisis - Titik Kristiyani (Faculty of Psychology Universitas Gadjah Mada, 2013)
Many studies of parental involvement in education have been conducted, which one of the purposed was to found the effect of parental involevement in education to student engagement in school, but the studies showed varied and conflicting result. This study is a meta analysis of correlation between parental involvement in education and student engagament in school, that want to make synthesis between that varied and conflicting result in the previous studies. The parental involvement in this study consist of all of parental behavior that showed involvement in teenager educational problem, both in the school and home area. There were 35 studies from 15 articles. Result showed that there was positive correlation between parental involvement in education and teenager student engagement.